New Y-SNPs in QM3 indigenous populations of Colombia - Espitia Fajardo, Marisol; Rivera Franco, Nelson; Braga, Yamid; Barreto, Guillermo (PLOS ONE, 2023)
In evolutionary studies of human populations based on the Y chromosome, the majority of Native Americans belong to the QM3 lineage. Therefore, to study the history of groups inhabiting northern South America, it is necessary to have a higher resolution of the tree. The objective of this work was to identify new SNPs of the QM3 lineage that would allow the evaluation of the phylogenetic relationships between Andean and Amazonian populations of Colombia. Sequences previously obtained from two Y chromosomes of Amazonian populations were used, from which 13 potential SNPs were selected and typed in 171 Amazonian samples from the Vaupés region and in 60 samples from the Pasto, Nasa, Embera, Arhuaco and Kogüi ethnic groups of the Andean region. In addition, the main SNPs/markers (L56, L54, M346, M848, Z780, CTS11780) defining autochthonous Q lineages were typed, along with others defined by different SNPs/markers as reported in the literature (CTS11357, SA05, Z19319, Z5915, and Z19384). It was found that all the new SNPs are present in the Amazonian samples and only 2 of them are shared with the Embera, Nasa and Pasto, but none with the Kogüi and Arhuaco from the northern Andes, in the Colombian Caribbean. Combining the 13 variants of the present study with 14 previously reported and using TMRCA, a new QM3 tree proposal is generated. This method makes it possible to increase the number of sublineages of QM3 with a higher resolution and to detect differences between the different populations of Vaupés in the Amazon, as in the case of the Kubeos and Pisamiras, the latter of which is in grave danger of extinction. These new sublineages are useful for microevolutionary studies of the Amerindian populations of South America.